Mengkritisi Ajaran Pietisme dalam Konteks Postmodern - Nggebu, Sostenis; Putra, Ando Pernando; Muslihin, Muslihin; Rapa, Chrisma Lilian; Selfi, Amanda; Ansju, David Alexander; Ririne, Yonas Frans; Bell, Michael Andreas (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
This study examines the doctrine of Pietism within the context of postmodern culture, highlighting a gap in the literature that connects the rich historical and spiritual heritage of Pietism with contemporary philosophical challenges. The central issue explored is how this revivalist movement, which emphasizes personal piety and lived religious experience, can maintain its relevance and authenticity amid the dominant postmodern tendencies of relativism and excessive individualism. The purpose of this research is to critically analyze the potentials and risks of Pietism in the postmodern era and to propose practical recommendations for Pietist church communities to remain contextually relevant without losing their theological essence. This study employs a literature review method by examining key theological and philosophical works. The findings indicate that Pietism remains relevant due to its focus on living faith (experientia) and ethical transformation expressed through love and service, which serve as antidotes to skepticism and religious formalism. However, the movement faces a significant risk of falling into excessive subjectivism when personal experience becomes detached from the objective truth of Scripture and the communal dimension of love.